1990
DOI: 10.1021/bk-1990-0421.ch023
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Resistance in Weeds and Crops

Abstract: This book focuses on the recent progress made in understanding the genetic and evolutionary mechanisms underlying herbicide resistance in weeds. Current controversies on key aspects of resistance evolution are discussed. The authors of Herbicide Resistance in Weeds and Crops highlight crucial present and future research directions and challenges connected with understanding of weed resistance development and the importance and impact of herbicide-resistant crops.The information provided in this book serves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 0 publications
0
69
0
3
Order By: Relevance
“…There is a prevailing opinion that the high glycoalkaloid content is connected with stress caused by drought, high temperatures or pesticides during vegetation (Leja 1987, Zrùst 1997. Sencor 70 WG (metribuzin) and Basagran 600 SL (bentazon) initially inhibit photosynthesis and transport of electrons in CO 2 reactions, which influences the metabolism of plants ( LeBaron andGressel 1982, Corbett 1994). The research findings by Zrùst (1997) showed that the increase in TGA content above the limit 200 mg/kg as a result of herbicide applications to control weeds and potato late blight should not cause any problems.…”
Section: Resultsmentioning
confidence: 99%
“…There is a prevailing opinion that the high glycoalkaloid content is connected with stress caused by drought, high temperatures or pesticides during vegetation (Leja 1987, Zrùst 1997. Sencor 70 WG (metribuzin) and Basagran 600 SL (bentazon) initially inhibit photosynthesis and transport of electrons in CO 2 reactions, which influences the metabolism of plants ( LeBaron andGressel 1982, Corbett 1994). The research findings by Zrùst (1997) showed that the increase in TGA content above the limit 200 mg/kg as a result of herbicide applications to control weeds and potato late blight should not cause any problems.…”
Section: Resultsmentioning
confidence: 99%
“…The s-triazine compounds have numerous applications throughout industry and agriculture (10,19,25,30). Those containing N-alkyl substituents, like atrazine (2-chloro-4-Nethylamino-6-N-isopropylamino-1,3,5-triazine), have been applied successfully as herbicides (3).…”
mentioning
confidence: 99%
“…The discovery of triazine resistance in Senecio vulgaris L. (23) and subsequently in other species (18) much lower affinity for triazine herbicides than the normal protein, resulting in triazine resistance (20). The altered QB protein in resistant biotypes reduces the rate of electron transfer between PSII quinone acceptors QA and QB, and thus, reduces the maximum rate of photosynthesis (4,17).…”
mentioning
confidence: 99%